Isolation and Characterization of Nitrate-Reducing Bacteria as Potential Probiotics for Oral and Systemic Health - Rosier, Bob T.; Moya-Gonzalvez, Eva M.; Corell-Escuin, Paula; Mira, Alex (Frontiers in Microbiology, 2020)
Recent evidence indicates that the reduction of salivary nitrate by oral bacteria can contribute to prevent oral diseases, as well as increase systemic nitric oxide levels that can improve conditions such as hypertension and diabetes. The objective of the current manuscript was to isolate nitrate-reducing bacteria from the oral cavity of healthy donors and test their in vitro probiotic potential to increase the nitrate-reduction capacity of oral communities. Sixty-two isolates were obtained from five different donors of which 53 were confirmed to be nitrate-reducers. Ten isolates were selected based on high nitrate-reduction capacity as well as high growth rates and low acidogenicity, all being Rothia species. The genomes of these ten isolates confirmed the presence of nitrate- and nitrite reductase genes and the absence of antimicrobial resistance, mobile genetic elements and virulence genes. The pH at which most nitrate was reduced differed between strains. However, a low pH always stimulated the reduction of nitrite compared to a neutral or slightly alkaline pH (p<0.01). We tested the effect of six out of 10 isolates on in vitro oral biofilm development in the presence or absence of 6.5 mM nitrate. Colonization of the isolates was confirmed by Illumina sequencing. The nitrate Reduction Capacity (NRC) of the bacterial communities increased when adding the isolates compared to controls without isolates (p<0.05). When adding nitrate (prebiotic treatment) or isolates in combination with nitrate (symbiotic treatment), a smaller decrease in pH due to sugar metabolism was observed (p<0.05), which for some symbiotic combinations appeared to be due to lactate consumption. Interestingly, there was a strong correlation between the NRC of oral communities and ammonia production even in the absence of nitrate (R=0.814, p<0.01), which indicates that bacteria involved in these processes are related. As observed in our study, individuals with an oral microbiota with a good NRC may benefit from nitrate as a prebiotic, while donors with a bad NRC may benefit from a symbiotic (nitrate + nitrate-reducing probiotic). Future clinical studies should test the effects of these treatments on oral and systemic health.